PERBANDINGAN PROFIT TESTING MODEL DETERMINISTIK DAN STOKASTIK PADA ASURANSI UNIT LINK - YUNITA, VALERIA TRISNA; WIDANA, I NYOMAN; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 7 No 2 (2018)DO - 10.24843/MTK.2018.v07.i02.p203, 2018)
Profit testing is a method to find out the potential loss or gain of unit link life insurance product. Unit-link life insurance is a combination of life insurance and investment. The aim of this research was to determine the potential benefits or losses of unit-linked life insurance products using a deterministic model and stochastic model. The calculation result using these model for a policy issued to a life aged 35, 45, and 55 and the benefit is paid till age 99  showed that the profit which   insurer can claim only for insurance issued to a life age 25 years old.